IMPORTANCE OF EXTRAMURAL VASCULAR INVASION IN PREOPERATIVE STAGING OF RECTAL CANCER WITH MRI - Ana Lazarova; Aleksandar Karagjozov (Македонско лекарско друштво = Macedonian medical association, 2018)
Introduction. Rectal cancer is the third most common malignant disease worldwide with a high mortality rate in developed countries. The prognosis of rectal cancer has been significantly improved over the past decade, and this is mainly due to progress in preoperative staging, which has been reflected in the therapeutic approach, where a significant change was made from simple surgical treatment to multimodal treatment. Although extramural vascular invasion (EMVI) is not included in the classical protocol for preoperative staging, itis a significant prognostic indicator of the recurrence rate. Methods. The study is a prospective one, and it included 61 hospital patients with previously proven rectal cancer, who had been operated on at the Department of Abdominal Surgery ofthe University Clinic for Surgical Diseases “St. Naum Ohridski” in Skopje, and who underwent a magnetic resonance staging preoperatively. Results. Comparison of extramural vascular invasion determined with MR preoperatively with pathohistological postoperatively obtained result. Conclusion. MR as an ideal imaging method in preoperative staging of rectal carcinoma. It is a tool that determines with high accuracy the extramural vascular invasion in patients with rectal cancer.
ЗНАЧЕЊЕТО НА ЕКСТРАМУРАЛНАТА ВАСКУЛАРНА ИНВАЗИЈА ВO ПРЕДОПЕРАТИВНИОТ СТЕЈЏИНГ НА РЕКТАЛЕН КАРЦИНОМ СО МАГНЕТНА РЕЗОНАНСА
Keywords: rectal cancer; magnetic resonance; preoperative staging; extramural vascular invasion